A new multiple-locus variable-number tandem repeat analysis reveals different clusters for Anaplasma phagocytophilum circulating in domestic and wild ruminants - Thibaud Dugat; Amélie Chastagner; Anne-Claire Lagrée; Elisabeth Petit; Benoît Durand; Simon Thierry; Fabien Corbière; Hélène Verheyden; Luc Chabanne; Xavier Bailly; Agnès Leblond; Gwenaël Vourc’h; et al. (Parasites & Vectors, 2014)
Abstract Background Anaplasma phagocytophilum is a tick-borne intragranulocytic alpha-proteobacterium. It is the causative agent of tick-borne fever in ruminants, and of human granulocytic anaplasmosis in humans, two diseases which are becoming increasingly recognized in Europe and the USA. However, while several molecular typing tools have been developed over the last years, few of them are appropriate for in-depth exploration of the epidemiological cycle of this bacterium. Therefore we have developed a Multiple-Locus Variable number tandem repeat (VNTR) Analysis typing technique for A. phagocytophilum. Methods Five VNTRs were selected based on the HZ human-derived strain genome, and were tested on the Webster human-derived strain and on 123 DNA samples: 67 from cattle, 7 from sheep, 15 from roe deer, 4 from red deer, 1 from a reindeer, 2 from horses, 1 from a dog, and 26 from ticks. Results From these samples, we obtained 84 different profiles, with a diversity index of 0.96 (0.99 for vertebrate samples, i.e. without tick samples). Our technique confirmed that A. phagocytophilum from roe deer or domestic ruminants belong to two different clusters, while A. phagocytophilum from red deer and domestic ruminants locate within the same cluster, questioning the respective roles of roe vs red deer as reservoir hosts for domestic ruminant strains in Europe. As expected, greater diversity was obtained between rather than within cattle herds. Conclusions Our technique has great potential to provide detailed information on A. phagocytophilum isolates, improving both epidemiological and phylogenic investigations, thereby helping in the development of relevant prevention and control measures.